Practical One-Pot Four-Step Synthesis of Isocoumarin-3-Carboxylic Acids - Vasylyshyn, Roman Y.; Demydchuk, Bohdan A.; Kovalenko, Sergiy M.; Matiychuk, Vasyl S.; Shishkina, Svetlana; Lukin, Oleg; Karpun, Yevhen; Shivanyuk, Alexander; Fetyukhin, Volodymyr M. (Synlett, 2025)
We report a facile and versatile, one-pot four-step synthesis of functionalized isocoumarin-3-carboxylic acids on a 70–100 g scale. Commercially available substituted anthranilic acids are converted into the corresponding 2-carboxydiazonium bromides, which subsequently undergo the CuBr-catalyzed Meerwein reaction with methyl-2-fluoroacrylate to afford 2-(2-bromo-2-fluoro-3-methoxy-3-oxopropyl)benzoic acids, whereas o-bromobenzoic acids are formed as minor impurities in the concomitant Sandmeyer reactions. The treatment of the reaction mixture with CH2Cl2 and aqueous NaHCO3 removes the salts of the o-bromobenzoic acids into the aqueous phase while 2-(2-bromo-2-fluoro-3-methoxy-3-oxopropyl)benzoic acids cyclize to give methyl 3-fluoro-isocoumarin-3-carboxylates whose trituration with AcOH/HCl/H3BO3 eliminates HF and hydrolyses the ester groups to afford substituted isocoumarin-3-carboxylic acids in overall 42–53% yield.
Keywords: Isocoumarin; One-pot synthesis; Meerwein reaction; Heterocyclization; Eliminations; Hydrolysis